Interoperability among healthcare organizations acting as certification authorities. - Bourka, A. (IEEE Transactions on information technology in biomedicine)
One of the main problems in public key infrastructures (PKI) is currently the lack of interoperability at international level, which is greatly dependent on the automation of the cross-certification procedure using certificate policies (CP). This paper addresses the aforementioned need by presenting a method for the automated development and comparison of CPs, with main emphasis on healthcare environments. The basic elements of this method include standardization of the CP content for healthcare, a prototype decision-making algorithm for CPs comparison, representation of CPs in extensible markup language, as well as a JAVA-based CP comparison tool. The final aim of the paper is to contribute toward the technical implementation of an on-line automated cross-certification service, yielding PKI interoperability and promoting information exchange between healthcare establishments.